DETERMINING FACTORS FOR THE PERFORMANCE OF AUDITOR EMPLOYEES AT THE BRI JAKARTA OFFICE III - Ana Ima Sofana; Yumhi (The Asia Pacific Journal Of Management Studies, 2024)
The purpose of this study is to determine whether work behavior, interpersonal communication, and job satisfaction all have an impact on performance. Using quantitative research, a saturation sample technique was used to survey 65 BRI Jakarta III auditor staff. With a questionnaire that employs correlation and regression data analysis techniques. The study's findings demonstrate that work behavior, interpersonal communication, and job happiness all have an impact on performance. Then, in partial testing, work behavior, interpersonal communication, and job happiness all have an impact on performance. According to research findings, businesses should consider work behavior characteristics, interpersonal communication, job satisfaction, and performance when planning and developing human resources for BRI Jakarta III auditor workers